Value Differentiation Between Enemies and Allies: Value Projection in National Images. Issue 1 (17th October 2012) - Eicher, Véronique; Pratto, Felicia; Wilhelm, Peter
<x xml:space="preserve">Abstract</x> The current study aimed to investigate value projection between Palestinians, Israelis, Americans, and Swiss as a function of their group's stance toward the Israeli‐Palestinian conflict. Drawing on image theory, we assumed that images—operationalized by value projection—would be a function not just of features of the target group, but of the rater group's relationship with the target group. Value projection can be seen as an indicator of (de)humanization as values represent goals and desirable behaviors of a person. We therefore expected higher projection to ally than to enemy groups, whereas we expected no difference in projection to out‐groups with neutral relations. Results show that allies did indeed project Security and Power to a higher degree to each other than to enemies, and enemies showed no, or even negative, projection onto each other. The ally of the enemy (Americans) was projected less negatively by Palestinians than vice versa, pointing to the higher complexity of third‐party images as opposed to the more classical ally and enemy images. As expected, Swiss students showed almost no difference in projection to the different out‐groups. These results confirm that the relationship between groups (e.g., alliance, enmity) rather than a consensual view of particular nations determines images.